Decapod crustaceans of the littoral and shallow sublittoral Iranian coast of the Persian Gulf: Faunistics, Biodiversity and Zoogeography - Naderloo, Reza; Türkay, Michael (Zootaxa, 2012)
A total of 150 species belonging to five infraorders (Caridea, Stenopodidea, Thalassinidea, Anomura and Brachyura) are recorded from the Iranian coast of the Persian Gulf. About 17% (26 species) are new records for the area. The infraorder Brachyura shows the highest species richness with 83 species. The Anomura and Caridea, with 29 and 27 species, respectively, follow. The Thalassinidea is represented by 10 species, whereas Stenopodidea only by one. The species with the highest occurence are ranked as follows: Nanosesarma sarii Naderloo & Türkay, 2009 (Brachyura), Alpheus lobidens De Haan, 1850 (Caridea), Metopograpsus messor (Forskål, 1775) (Brachyura), Coenobita scaevola (Forskål, 1775) (Anomura), Diogenes avarus Heller, 1865 (Anomura), Pilumnopeus convexus Maccagno, 1936 (Brachyura) and Portunus segnis (Forskål, 1775) (Brachyura). Among the surveyed habitats, mixed rocky/cobble show the highest diversity with 99 (66%) recorded species, followed by sedimentary muddy-sandy substrates and mangroves with 40 (26%) and 24 species (16%), respectively. The least diverse habitat is sandy beaches with 6 species. The decapod fauna shows a predominance of wide ranging Indo-West Pacific species (43%) and a small degree of endemism (5%). A considerable number of species is restricted to the northwestern Indian Ocean (27%), supporting the presence of a zoogeographical subregion within the western Indian Ocean Province.